2023
DOI: 10.1002/pei3.10122
|View full text |Cite
|
Sign up to set email alerts
|

Halomonas ventosae JPT10 promotes salt tolerance in foxtail millet (Setaria italica) by affecting the levels of multiple antioxidants and phytohormones

Shenghui Xiao,
Yiman Wan,
Yue Zheng
et al.

Abstract: Plant growth‐promoting bacterias (PGPBs) can increase crop output under normal and abiotic conditions. However, the mechanisms underlying the plant salt tolerance‐promoting role of PGPBs still remain largely unknown. In this study, we demonstrated that Halomonas ventosae JPT10 promoted the salt tolerance of both dicots and monocots. Physiological analysis revealed that JPT10 reduced reactive oxygen species accumulation by improving the antioxidant capability of foxtail millet seedlings. The metabolomic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
0
0
Order By: Relevance
“…In separate studies, several other Halomonas strains have been shown to enhance salt tolerance in purple basil [111], maize [112], chickpea [131], and sunflower [114]. One Halomonas strain, H. ventosae JPT10, was tested with multiple plants and enhanced salt tolerance in foxtail millet, soybean, tomato, wheat, and maize [115], indicating that some strains may serve as PGPB for multiple crop species. In earlier work, our research group isolated many halophilic bacteria from halophytes near Utah Lake in Utah, including Halomonas and Kushneria strains, some of which were found to have ST-PGPB activity [102].…”
Section: Salt-tolerant Bacterial Genus Halomonasmentioning
confidence: 99%
“…In separate studies, several other Halomonas strains have been shown to enhance salt tolerance in purple basil [111], maize [112], chickpea [131], and sunflower [114]. One Halomonas strain, H. ventosae JPT10, was tested with multiple plants and enhanced salt tolerance in foxtail millet, soybean, tomato, wheat, and maize [115], indicating that some strains may serve as PGPB for multiple crop species. In earlier work, our research group isolated many halophilic bacteria from halophytes near Utah Lake in Utah, including Halomonas and Kushneria strains, some of which were found to have ST-PGPB activity [102].…”
Section: Salt-tolerant Bacterial Genus Halomonasmentioning
confidence: 99%